(untitled) (Journal of Bangladesh Institute of Planners, 2013)
Road traffic accidents are the world’s number one cause of death among young people between 16 and 24. Bangladesh has one of the highest fatality rate in road accidents in the world. Moreover, Dhaka, the capital of Bangladesh, is the most vulnerable city both in terms of total number of accidents and accident rates. A total number of 2,720 accidents occurred within 2007-2011. This has caused a total of 1,481 numbers of pedestrian fatal accidents with 1,562 pedestrian fatal casualties. At this backdrop, road safety problem has become one of the major issues for the transport regulators and traffic law enforcers in Dhaka. The objective of this research is to identify the most accident-prone roads, the victims as well the in-depth reasons for traffic accident in Dhaka Metropolitan Area. In this article, the road safety situation and traffic accident trends are discussed elaborately. It also discusses some contemporary issues and priorities in addressing the road safety problems. Based on the findings of this study, some recommendations related to Engineering, Enforcement, Educational and Emergency Response aspects are made. This kind of research will help generating new ideas to find out the parameters for reducing road traffic accidents in greater Dhaka City. Vol. 6, December 2013, pp. 103-118